[{Ni4(OH)3AsO4}4(B‐α‐PW9O34)4]28−: A New Polyoxometalate Structural Family with Catalytic Hydrogen Evolution Activity. Issue 48 (8th October 2015) - Lv, Hongjin; Chi, Yingnan; van Leusen, Jan; Kögerler, Paul; Chen, Zheyuan; Bacsa, John; Geletii, Yurii V.; Guo, Weiwei; Lian, Tianquan; Hill, Craig L.
Abstract: A new structural polyoxometalate motif, [{Ni4 (OH)3 AsO4 }4 ( B ‐α‐PW9 O34 )4 ] 28−, which contains the highest nuclearity structurally characterized multi‐nickel‐containing polyanion to date, has been synthesized and characterized by single‐crystal X‐ray diffraction, temperature‐dependent magnetism and several other techniques. The unique central {Ni16 (OH)12 O4 (AsO4 )4 } core shows dominant ferromagnetic exchange interactions, with maximum χ m T of 69.21 cm 3  K mol −1 at 3.4 K. Significantly, this structurally unprecedented complex is an efficient, water‐compatible, noble‐metal‐free catalyst for H2 production upon visible light irradiation (photosensitizer=[Ir(ppy)2 (dtbbpy)][PF6 ]; sacrificial electron donor=triethylamine or triethanolamine). The highest turnover number of approximately 580, corresponding to a best quantum yield of approximately 4.07 %, is achieved when using triethylamine as electron donor in the presence of water. The mechanism of this photodriven process has been probed by time‐solved luminescence and by static emission quenching. Abstract : Welcome to the family : The multi‐nickel carbon‐free polyoxometalate complex, [{Ni4 (OH)3 AsO4 }4 ( B ‐α‐PW9 O34 )4 ] 28−, the highest nuclearity structurally characterized multi‐nickel‐containing polyanion developed to date, was synthesized by using a facile, high‐yield, one‐pot method and is an efficient, noble‐metal‐free catalyst for H2 production under visible‐light irradiation.